Educating girls in Congo: An unsolved pedagogical paradox since colonial times?. Issue 8 (November 2018) - Depaepe, Marc; Lembagusala Kikumbi, Annette
Generally speaking, colonial education in Congo did not engender a very great widening of consciousness among the local population. Mostly, it resulted in inevitable submission through discipline and order. This was particularly the case for girls, for which fewer initiatives were taken than for boys. Moreover, gender stereotypes from the 'mother' country clearly dominated the evolution of female education in Congo. At best girls were trained for care-taking professions. After independence, some Congolese leaders, like Mulele (the first Minister of Education of the Democratic Republic of Congo) and Mobutu (who called himself 'the founding president of Zaire') wanted to break the colonial tradition by putting education in a more authentic African context. However, both educational models – the one of Mulele as well as the one of his adversary Mobutu - were in the end not very successful. The least we can say, at the basis of some oral history, is that the pedagogical paradox between the rhetoric of emancipation and the existing everyday educational realities in Africa is far from being solved.